Mammon Machine: a publicidade dos bancos - valor, imunização, diálogo - Costa, Alan Faquinetti da (2022)
This thesis aims to: study the transformations in the construction of corporate identities in large retail banks; identify if there is in our object of study, amely, the corporate communication of traditional banks, a recent change in the strategy of creating institutional identities that would privilege another form of communication and; to identify traces of this strategy in the recent communication of these financial institutions. We justify the importance of this research with the fact that banks are powerful actors in the economy and politics and, therefore, need to be observed. Banco do Brasil, Bradesco, Itaú, Caixa Econômica Federal and Santander, five traditional banks, were chosen as empirical objects. Based on a study by a German consultancy, which concluded that these companies will need to close 30% of their branches in 3 years, we justify the hypothesis that graphic brands have lost communicative relevance which has been replaced by other persuasive characteristics. In other words, the given signage characteristics that permeated the brands and chromatic chords on the facades of the banks is losing relevance and being replaced by a new form of persuasion. Less “we are here” and more “we are here to listen to you.” The conclusion reached from this research suggests that, although the inflection in the advertising strategy that we sought to confirm was not absolutely clear after our empirical analysis, it is notable that the banks' messages navigate between immunization and dialogue, most of the time reserving for enunciators an intimate role, as a friend or family member who would not hesitate to cooperate with their enunciatee. Our theoretical framework is constituted by: Niall Ferguson, Gilles Lipovetsky and Zygmunt Bauman, who support the historical reflections about banks and consumption; Lucrécia D'aléssio Ferrara, Richard Sennett, Giorgio Agamben, Leo Huberman and André Gorz and their observations on the dematerialization of two important concepts of economic theory, value and labor; Vilém Flusser, Michel Foucault and Jean Baudrillard who bring their reflections on the transformation of value into meaning; Mikhail Bakhtin and his theories on dialogism, commented here by Richard Sennett, Michael Hardt and Antonio Negri; Deleuze and Guattari with their theory about percepts and affects and; Thomas Hobbes and Roberto Esposito, who underpin our analysis of power and immunization